1981
DOI: 10.1126/science.6782674
|View full text |Cite
|
Sign up to set email alerts
|

Giant Polytene Chromosomes from the Ovaries of a Drosophila Mutant

Abstract: The chromosomes of the ovarian nurse cells of Drosophila melanogaster fall apart during their cycles of endoreduplication. However, chromosomal synapsis occurs in the pseudonurse cells produced in certain mutant females. The resulting polytene chromosomes undergo developmental changes that are strikingly different from those recorded for the giant chromosomes of the larval salivary gland cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
1

Year Published

1982
1982
2007
2007

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 5 publications
0
21
0
1
Order By: Relevance
“…Interestingly, the onset of this staining pattern coincides with the beginning of the endo-reduplication cell cycle in nurse cells, during which DNA replication occurs repeatedly in the absence of cell division. We observe these SMC1/3 finger-like projections during early vitellarial stages when the polyploid nurse cell chromosomes exhibit polyteny, the precise alignment of multiple copies of sister chromatids (King et al, 1981). Unlike polytene chromosomes in the Drosophila salivary gland, nurse cell polytene chromosomes are short-lived.…”
Section: Enrichment Of Cohesin Smcs At the Centromeres Of Meiotic Chrmentioning
confidence: 89%
“…Interestingly, the onset of this staining pattern coincides with the beginning of the endo-reduplication cell cycle in nurse cells, during which DNA replication occurs repeatedly in the absence of cell division. We observe these SMC1/3 finger-like projections during early vitellarial stages when the polyploid nurse cell chromosomes exhibit polyteny, the precise alignment of multiple copies of sister chromatids (King et al, 1981). Unlike polytene chromosomes in the Drosophila salivary gland, nurse cell polytene chromosomes are short-lived.…”
Section: Enrichment Of Cohesin Smcs At the Centromeres Of Meiotic Chrmentioning
confidence: 89%
“…The otu gene is one of several genes whose products are required for the determination and differentiation of oocytes and nurse cells (19,21,22,25). Homozygous mutant otu females are sterile and display a variety of abnormalities with respect to oocyte and nurse cell development.…”
mentioning
confidence: 99%
“…The otu gene is one of several genes whose products are required for the determination and differentiation of oocytes and nurse cells (19,21,22,25 gene is expressed, and its product is required, in the germ cells of the ovary (48). Two independent studies have also shown that the alleles otu4 and otu7 are germ cell autonomous (unpublished data [21]).…”
mentioning
confidence: 99%
“…Journal of Cell Science 116 (6) (King et al, 1981). This gene influences egg chamber formation, the system of actin microfilaments and the transfer of substances from NCs to the growing oocyte (Storto and King, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…In D. melanogaster, mutation otu causes formation of polytene chromosomes in NCs (King et al, 1981), which show greater polytenization of heterochromatic sequences than in SGs (Mal'ceva and Zhimulev, 1993;Koryakov et al, 1996).…”
mentioning
confidence: 99%